2020
DOI: 10.1002/mabi.202000149
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer Cylindrical Conduit Consisting of Electrospun Polycaprolactone Nanofibers and DSC Cross‐Linked Sodium Alginate Hydrogel to Bridge Peripheral Nerve Gaps

Abstract: Herein, a bilayer cylindrical conduit (P‐CA) is presented consisting of electrospun polycaprolactone (PCL) nanofibers and sodium alginate hydrogel covalently cross‐linked with N,N′‐disuccinimidyl carbonate (DSC). The bilayer P‐CA conduit is developed by combining the electrospinning and outer–inner layer methods. Using DSC, as a covalent crosslinker, increases the degradation time of the sodium alginate hydrogel up to 2 months. The swelling ratio of the hydrogel is also 503% during the first 8 h. The DSC cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Electrospun hydrogels based on both natural polymers such as collagen, gelatin, dextran, alginate, HA, or chitosan as well as synthetic polymers such as POEGMA ( Xu et al, 2016 ) have been reported, with other synthetic polymers such as poly (ethylene oxide) (PEO), poly (vinyl pyrrolidone) (PVP), or poly (vinyl acetate) (PVA) also in some cases included to promote chain entanglement in the precursor polymer solution and thus nanofiber formation instead of particle sprays. Stiffer degradable polymers such as poly (ε-caprolactone) (PCL) may also be added to increase the mechanical strength of the porous hydrogel scaffold, a key challenge with electrospinning ( Koosha and Mirzadeh, 2015 ; Xu et al, 2016 ; Majidi et al, 2018 ; Wakuda et al, 2018 ; Askarzadeh et al, 2020 ). Table 1 summarizes different materials and methods used for electrospinning hydrogels.…”
Section: Emerging Fabrication Techniques For Hydrogel-based Tissue Sc...mentioning
confidence: 99%
“…Electrospun hydrogels based on both natural polymers such as collagen, gelatin, dextran, alginate, HA, or chitosan as well as synthetic polymers such as POEGMA ( Xu et al, 2016 ) have been reported, with other synthetic polymers such as poly (ethylene oxide) (PEO), poly (vinyl pyrrolidone) (PVP), or poly (vinyl acetate) (PVA) also in some cases included to promote chain entanglement in the precursor polymer solution and thus nanofiber formation instead of particle sprays. Stiffer degradable polymers such as poly (ε-caprolactone) (PCL) may also be added to increase the mechanical strength of the porous hydrogel scaffold, a key challenge with electrospinning ( Koosha and Mirzadeh, 2015 ; Xu et al, 2016 ; Majidi et al, 2018 ; Wakuda et al, 2018 ; Askarzadeh et al, 2020 ). Table 1 summarizes different materials and methods used for electrospinning hydrogels.…”
Section: Emerging Fabrication Techniques For Hydrogel-based Tissue Sc...mentioning
confidence: 99%
“…[265] Likewise, core-shell PCL-alginate electrospun NFs were proposed as substitutes for peripheral nerves. [266] These composite NFs promoted water absorption and biological activity of the neural precursors, leading to fasttracking of the sciatic nerve repair in a rat model. The nearfield electrospinning of alginate was also demonstrated.…”
Section: Tissue Engineering and Wound Healingmentioning
confidence: 99%
“…Alginate is also used successfully as a conduit internal filler for growth factor delivery in nerve regeneration ( Ohta et al, 2004 ; Pfister et al, 2007b , 2008 ) and for molecule controlled release at various pH values ( Augst et al, 2006 ; Gao et al, 2009 ; Jeon et al, 2009 ). In particular, alginate as internal filler leaves no residue 4 months after surgery in a cat model of 50 mm gap sciatic nerve injury repaired with tubulation ( Sufan et al, 2001 ) and is also able to promote specifically adhesion and proliferation of nerve cells in rats with 10 mm sciatic nerve gap 7 weeks after surgery ( Askarzadeh et al, 2020 ).…”
Section: Natural-based Biomaterialsmentioning
confidence: 99%